Combinations of Abiotic Factors Differentially Alter Production of Plant Secondary Metabolites in Five Woody Plant Species in the Boreal-Temperate Transition Zone - Berini, John L.; Brockman, Stephen A.; Hegeman, Adrian D.; Reich, Peter B.; Muthukrishnan, Ranjan; Montgomery, Rebecca A.; Forester, James D. (Frontiers in Plant Science, 2018)
Plant secondary metabolites (PSMs) are a key mechanism by which plants defend themselves against potential threats, and changes in the abiotic environment can alter the diversity and abundance of PSMs. While the number of studies investigating the effects of abiotic factors on PSM production is growing, we currently have a limited understanding of how combinations of factors may influence PSM production. The objective of this study was to determine how warming influences PSM production and how the addition of other factors may modulate this effect. We used untargeted metabolomics to evaluate how PSM production in five different woody plant species in northern Minnesota, USA are influenced by varying combinations of temperature, moisture, and light in both experimental and natural conditions. We also analysed changes to the abundances of two compounds from two different species – two resin acids in Abies balsamea and catechin and a terpene acid in Betula papyrifera. We used perMANOVA to compare PSM profiles and phytochemical turnover across treatments and NMDS to visualize treatment-specific changes in PSM profiles. We used linear mixed-effects models to examine changes in phytochemical richness and changes in the abundances of our example compounds. Under closed-canopy, experimental warming led to distinct PSM profiles and induced phytochemical turnover in B. papyrifera. In open-canopy sites, warming had no influence on PSM production. In samples collected across northeastern Minnesota, regional temperature differences had no influence on PSM profiles or phytochemical richness but did induce phytochemical turnover in B. papyrifera and Populus tremuloides. Throughout northeast Minnesota, warmer temperatures combined with open canopy resulted in distinct PSM profiles for all species and induced phytochemical turnover in all but Corylus cornuta. Although neither example compound in A. balsamea was influenced by any of the abiotic conditions, both compounds in B. papyrifera exhibited significant changes in response to warming and canopy. Our results demonstrate that the metabolic response of woody plants to combinations of abiotic factors cannot be extrapolated from that of a single factor. This heterogeneous phytochemical response directly affects interactions between plants and other organisms and may yield unexpected results as plant communities adapt to novel environmental conditions.